2010
DOI: 10.1007/s11085-010-9219-1
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Metastable to Alpha Transformation of Al2O3 Scale on Fe–Al Alloy by Pure-Metal Coatings at 900 °C

Abstract: The effect of pure-metal coatings on the transformation of a pre-formed h-Al 2 O 3 scale on an Fe-50Al alloy was investigated. The elements Fe, Cr, Ti, and Ni were deposited on the pre-formed Al 2 O 3 having a thickness of about 50 nm. Ti, Cr or Fe coatings on pre-formed h-Al 2 O 3 were found to accelerate the transformation to a-Al 2 O 3 , while no apparent effect was observed from the Ni coating. Since the corundum crystal structure of Ti 2 O 3 , Cr 2 O 3 and Fe 2 O 3 was indentified on Ti, Cr or Fe coated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…On the other hand, the formation, topography, compactness and crystal type of the Al 2 O 3 film formed on the FeAl layer depend on the alloying elements. Just as argued by Kitajima et al [78], Ti, Fe and Cr could promote the transformation from q-Al 2 O 3 to a-Al 2 O 3 on Fee50Al alloys because their oxides could act as heterogeneous nucleation sites for a-Al 2 O 3 ; while Ni almost had no apparent effect. Since the typical aluminide coatings prepared on steels are composed of a FeAl transition layer and an outer Al 2 O 3 film, it can be inferred from above statements that the alloying elements in the steel substrates must have some influences on the coatings.…”
Section: Substrate Effectmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, the formation, topography, compactness and crystal type of the Al 2 O 3 film formed on the FeAl layer depend on the alloying elements. Just as argued by Kitajima et al [78], Ti, Fe and Cr could promote the transformation from q-Al 2 O 3 to a-Al 2 O 3 on Fee50Al alloys because their oxides could act as heterogeneous nucleation sites for a-Al 2 O 3 ; while Ni almost had no apparent effect. Since the typical aluminide coatings prepared on steels are composed of a FeAl transition layer and an outer Al 2 O 3 film, it can be inferred from above statements that the alloying elements in the steel substrates must have some influences on the coatings.…”
Section: Substrate Effectmentioning
confidence: 78%
“…Nevertheless, Fe atoms and other doped alloying elements are also likely to be oxidized to form the corresponding oxides. For example, apart from Al 2 O 3 , NiO and TiO 2 formed on the Ni and Ti predeposited FeAl surface after oxidizing at 900 C, respectively [78]. Zhan et al [82] also found that a little CeO 2 existed in the Al 2 O 3 film formed on CLAM steels with the addition of Ce during the PC aluminization.…”
Section: Doping Effectmentioning
confidence: 99%
“…Regarding the effect of Fe and Ni on the phase transformation of Al 2 O 3 scale, we found that a thin-Fe coating, *100 nm, completely suppressed the metastable Al 2 O 3 scale formation on Fe-and Ni-based alloys, but a Ni-coating delayed the transformation to a-Al 2 O 3 [14][15][16]. Initial formation of Fe 2 O 3 , which is isomorphous structure with a-Al 2 O 3 , promoted the transformation, but NiO formation retarded the transformation, which is likely due to the stabilization of metastable Al 2 O 3 [14].…”
Section: Introductionmentioning
confidence: 85%
“…After being incorporated into the growing scale, Y or Ce ions from Y 2 O 3 /CeO 2 nanoparticles in the alumina scale segregate to the scale grain-boundaries and then transport outwards, driven by the oxygen potential gradient between the interfaces of the metal/scale and the scale/gas [16] . In this case, a different effect [3][4][5][6][7][8][9][14][15][16][17][18] on the - transformation occurred. In this experiment, Y significantly hinders the outward short-circuit diffusion of the Al for the growth of the -alumina, thus a lower oxidation rate with shorter -alumina whiskers being observed.…”
Section: Discussionmentioning
confidence: 99%